PROYEKSI PRODUKSI BERAS DAN STRATEGI MEWUJUDKAN SWASEMBADA BERAS DI KABUPATEN KETAPANG - Novira Kusrini, Hendri Sibuea, Erlinda Yurisinthae, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2014)
Total rice production in Ketapang District compared with other districts in West Kalimantan is quite high, which is take the the fourth place in rice producing district in West Kalimantan Province. However, based on the development of rice production number is also known that rice production in Ketapang District experienced a significant decline, from a range of more than 100,000 tons per year down to less than 100,000 tons per year starting in 2008 (BPS Ketapang District, 2011) . Based on its development , the rate of change in the availability of rice in Ketapang very volatile and tends to decrease, while the rate of population increase. This needs to be a concern because the population rate will always increase, so it must be balanced with stability increase of rice production, to fulfill the basic needs of the staple food of the community . Based on the problem, this research aims to provide the projection of rice production and consumption in the next seven years and its implications for self-sufficiency in rice and to formulate appropriate strategies that should be implemented in order to achieve self-sufficiency in rice in Ketapang District. Analysis of projected production and consumption of rice in Ketapang calculated using Sofware Analysis of Food Consumption Patterns, with trend analysis approach, by considering the changes of the amount of food production and consumption within the last 5 years to predict the amount of rice production and consumption in the next 7 years. The data used are secondary data from annual data from BPS, namely Ketapang in Numbers 2007-2011. As for formulating strategies in order to achieve self-sufficiency in rice used SWOT analysis . The analysis showed that the district can achieve rice surplus in 2016 if the rice harvested area and productivity can be increased respectively by 3 % and 5 %, while still retaining the decline in rice consumption by 0.75 % per year. Based on the results of the SWOT analysis appropriate strategy to be applied is progressive strategy, by focusing on the strength of Ketapang District. Thus, the formulation of a strategy that gained intensification and extension of land, diversification of food in community and institutional strengthening. Key words : projections of production , self-sufficiency in rice